A Curious Feature of Regression. (1st May 2017) - Lutzer, Carl V.
Summary: In this article, we investigate how repeating a data point affects the least-squares regression. While it is well known that the regression line approaches the repeated point, the fact that it pivots surprises many people. The article uses linear algebra to explore this behavior, develops relevant formulas for the pivot point, and explains the essential connection between the pivot point to the set of data.